Gold leaching by use of an N,N '-disubstituted thiourea - (:unkn) unknown (MARCEL DEKKER INC, 2001)
A novel reagent for gold leaching was synthesized and the leaching conditions investigated. The reagent, 1-phenyl-2-thio-3-(2-hydroxyethyl) urea, dissolved gold at relatively high yields (>95%) in the presence of an oxidant (Fe(III)) in a sulfuric acid solution at pH 0.9-1.2 at room temperature. The effects of certain leaching parameters, such as working pH, reagent-Au mol ratio, oxidant-Au mol ratio, contact time, and temperature are discussed.
Keywords: gold leaching; thioureation; PRECIOUS METALS